The Role of Transcranial Doppler Sonography in the Management of Pediatric Hydrocephalus - Kolarovszki, Branislav (IntechOpen, 2019)
Negative influence of cerebral circulation with the emergence of cerebral hypoperfusion plays a significant role in the pathophysiology of pediatric hydrocephalus. Transcranial Doppler sonography is a non-invasive method for indirectly measuring intracranial pressure and decreasing intracranial compliance by assessing changes of cerebral circulation. This book discusses the cerebral circulation and intracranial dynamics in pediatric hydrocephalus. It also focuses on evaluating the impact of various intracranial factors on Doppler parameters of cerebral circulation, especially in neonates with hydrocephalus. The ambition of this work is to improve indication and timing of drainage procedure in children with hydrocephalus by applying scientific results and clinical experience.